EKSPLOITASI SEKSUAL ANAK YANG DIJADIKAN PELACUR OLEH ORANGTUA - Muhammad Aswin Akbar (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACTThe crime of sexual exploitation of children used as prostitutes by their parents indicates that the protection of children's rights clearly stipulated in the relevant laws and regulations has not been implemented by their parents, this will hamper their mental growth and good thinking patterns in their children. So that it is only implied a shortcut to get money easily by becoming prostitutes at a very young age. From research and analysis on criminal acts concerning Sexual Exploitation of Children, data analysis is used with the Law of the Republic of Indonesia No.35 of 2014 concerning Changes to Law No. 23 of 2002 concerning Child Protection, Law of the Republic of Indonesia No.39 of 1999 concerning Human Rights, Decree of the President of the Republic of Indonesia No .87 of 2002 concerning the National Action Plan for the Elimination of Commercial Sexual Exploitation of Children on 30 December 2002. To enforce legal regulations relating to the sexual exploitation of children who are used as prostitutes by their parents, there must be a structural substance that must work together. Keywords: Sexual Exploitation of Children, Prostitutes, Parents.